2020
DOI: 10.1016/j.yjmcc.2020.08.017
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs targeting the SARS-CoV-2 entry receptor ACE2 in cardiomyocytes

Abstract: The World Health Organization (WHO) declared coronavirus disease 2019 (COVID-19) as a public health emergency of international concern as more than 15 million cases were reported by 24th July 2020. Angiotensinconverting enzyme 2 (ACE2) is a COVID-19 entry receptor regulating host cell infection. A recent study reported that ACE2 is expressed in cardiomyocytes. In this study, we aimed to explore if there are microRNA (miRNA) molecules which target ACE2 and which may be exploited to regulate the SARS-CoV-2 recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
103
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(106 citation statements)
references
References 17 publications
2
103
0
1
Order By: Relevance
“… Germany To identify miRNAs predicted to regulate ACE2 using an in-silico approach. ( Lu et al, 2020 ) 25 Zhang H July 15, 2020. US To gain insight into the expression of ACE2 in the human airway epithelia, including miRNA regulatory activity.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… Germany To identify miRNAs predicted to regulate ACE2 using an in-silico approach. ( Lu et al, 2020 ) 25 Zhang H July 15, 2020. US To gain insight into the expression of ACE2 in the human airway epithelia, including miRNA regulatory activity.…”
Section: Resultsmentioning
confidence: 99%
“… Downregulation in the small airway epithelium of smokers compared to non-smokers Targets the 3’UTR sequence of ACE2 mRNA miR-200c-3p ACE2 Induced overexpression resulted in downregulation of ACE2 in human cardiomyocytes. Lu et al, 2020 , Nersisyan et al, 2020b . Interaction with ACE2 was validated in HEK-293 T cells by luciferase reporter assay miR-125a-5p ACE2 Expressed in lungs, kidney and esophagus.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The in vitro cell culture and tissue models will also be helpful in studying SARS-CoV-2 infection, cytotoxicity, molecular mechanisms, and drug or therapy effects on cells. As multiple studies have shown, the iPSC-derived cardiomyocytes could be transfected by SARS-CoV-2 and develop cytotoxic effects and death [ 61 , 136 , 137 , 138 , 139 , 140 ]. The use of cardiac organoids will be instructive to mimic COVID-19 infection of the heart but, as of now, there is no study available.…”
Section: Limitations Of Animal Modelsmentioning
confidence: 99%
“…31 miRNAs and 29 miRNAs can downregulate hypothalamic ACE2 and TMPRSS2 gene expression, respectively, suggesting that they might be useful in treating SARS-CoV-2 neuroinvasion, by blocking virus entry [36]. In another study, miR-200 c suppressed ACE2 mRNA and protein expression in rat primary cardiomyocytes and human-induced pluripotent stem cell-derived cardiomyocytes, suggesting a promising strategy to treat SARS-CoV-2 cardiovascular complications [37].…”
Section: Attachment and Entrymentioning
confidence: 98%